Micropropagation of Duboisia Species via Shoot Tip Meristem - Yuxin Xue; Jayeni Chathurika Amarathunga Hiti-Bandaralage; Dilani Tharanga Jambuthenne; Zizhu Zhao; Neena Mitter (Horticulturae, 2023)
Duboisia is an Australian native, commercially valuable for tropane alkaloid extraction. Clonal propagation of elite selections is essential to establish highly productive plantations. The current propagation system using stem cuttings is proven to be inefficient, prompting the industry to seek a more efficient and effective propagation tool. Tissue culture is a cost-effective alternative for mass propagation of true-to-type plants, particularly ideal for propagating elite Duboisia selections. In this context, attempts were made to develop a commercially viable high throughput micropropagation system for three Duboisia species: Duboisia myoporoides, Duboisia leichhradtii and Duboisia hopwoodii. Various nutrient media, hormone combinations and incubating conditions were tested to optimise each stage of the micropropagation pipeline. The findings revealed that the tissue culture media composition and hormone requirements are species-specific. With the optimised conditions, an efficient tissue culture system was developed, achieving successful meristem induction and multiplication. Species-specific rooting protocol optimisation resulted in 100% rooting for D. myoporoides and D. leichhardtii, and 70% rooting for D. hopwoodii. Furthermore, an optimised acclimatisation protocol supported 100% survival of D. myoporoides and D. leichhardtii and 80% of D. hopwoodii plantlets. This study, for the first time, demonstrated the capacity of successful meristem culture of three Duboisia species, establishing the foundation for high throughput micropropagation of Duboisia species.